Location, Function, Boundaries: Tracking the History of Urban Expansion in Hanoi, 1960-2020 - Vu, Hoai Duc; Do, Thi Huong Lan; Hoang, Thi Thanh Thuy (International Planning History Society Proceedings, 2024)
Urban expansion planning plays a pivotal role in orchestrating the potential development of urban spaces while accommodating the increasing population demands and fostering sustainable urban development. This paper focuses on Hanoi’s urban expansion planning practice from 1960-2020, dividing into three different stages with seven proposals: 1) the first stage(1960-1975), the planner uses a monocentric urban model in the Finger Plan; 2) the second stage(1975-1986) reflects two different planning approaches, one was inspired by planning techniques employed in the Soviet Union to develop a new center which located 30-50km away from the existing city, the other was inherited proposals from the 1960s; 3) the third stage(1986-2020) evolves a comprehensive model which combined polycentric urban model with green belts and new towns. The paper particularly analyzes the location, function, and boundaries of urban expansion areas of Hanoi by using primary and secondary materials from the Vietnam Institute for Urban and Rural Planning, the Ministry of Construction,etc. It reveals that urban expansion proposals in Hanoi are politically driven, and lack science due to relying on inaccurate population and economic forecasts.